2021
DOI: 10.1177/25148486211066388
|View full text |Cite
|
Sign up to set email alerts
|

Conserving inequality: How private conservation and property developers ‘fix’ spatial injustice in South Africa

Abstract: In 2016, South Africa launched its National Biodiversity Economy Strategy. This strategy aims to facilitate the development of a ‘wildlife economy’ as a solution to unemployment, loss of biodiversity and rural development. Central to the strategy is the role of private conservation actors, who keenly posit their commercial model as the best way to achieve these objectives. This stands in sharp contrast to recent critiques that suggest that private conservation reinforces structural inequality by denying access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…as entrenching apartheid legacies and racial inequities 3,4 , they support the claim that wildlife ranching results in more and better paid jobs than agricultural ranches. However, most of the studies cited as proof are based on self-reported data by wildlife ranch owners or managers 5,6 .…”
Section: Marja Spierenburgmentioning
confidence: 54%
See 1 more Smart Citation
“…as entrenching apartheid legacies and racial inequities 3,4 , they support the claim that wildlife ranching results in more and better paid jobs than agricultural ranches. However, most of the studies cited as proof are based on self-reported data by wildlife ranch owners or managers 5,6 .…”
Section: Marja Spierenburgmentioning
confidence: 54%
“…The impacts of trophy hunting and ecotourism wildlife ranches have been particularly devastating for farm workers and dwellers, for whom the farms historically not only were places of work but also home -farmers were able to keep wages low by allowing farm workers to live and cultivate on their land. With wildlife ranches, many workers are instead forced into the expanding informal settlements dotting the South African countryside 1,3,4,6 . It is quite dangerous to argue that wildlife ranching in general seems to be a resilient form of land use when the social costs of the adaptive strategies of especially hunting and ecotourism ranches are so high.…”
Section: Marja Spierenburgmentioning
confidence: 99%
“…trophy hunting) and today there is an increase in philanthropic initiatives in tourism (Koot, 2021). Importantly, the wildlife economy's focus is centred on a private property regime, which has led to an increase in structural inequality and unjust labour circumstances for many (Thakholi and Büscher, 2021).…”
Section: Historical Development Of Hoedspruit and Surroundingsmentioning
confidence: 99%
“…This perception of safety further increases Hoedspruit's market value, which is directly related to the unwillingness to sell land for affordable or social housing. One wildlife estate manager, for instance, declared how fortunate it was that prior plans to develop affordable housing on the estate lands had been thwarted, because this 'would have killed the town', lead to an influx of poor people, too many houses and 'chaos' (see Thakholi and Büscher, 2021). This reference to a lower class has a strong racial connotation, since Hoedspruit is an overwhelmingly white and well-off town, while nearly all 'poor people' are black.…”
Section: Class and Racial Enclosuresmentioning
confidence: 99%
“…Discursive power and green grabbing processes provide theoretical and empirical breakthroughs to analyse these asymmetrical social relations and how the same configure the everyday interaction of people and forest resources. There is less discussion on existing capitalist uneven power influencing social and spatial-fix of climate crisis (Bryant, Dabhi & Böhm, 2015;Scheba, 2014;Thakholi & Büscher, 2021).…”
Section: Dispossession and Contestations In The Enactment Of Redd+: '...mentioning
confidence: 99%